Exergetic performance analysis of low GWP refrigerants as an alternative to R410A in split air conditioner. (2022) - Mishra, Punit; Soni, Shubham; Maheshwari, Govind
Abstract: In the present analysis, five alternative refrigerants namely R32, R447A, R447B, R452B, and R454B have been analysed based on exergy to find an alternative of high global warming potential refrigerant R410A, in a split air conditioner. Evaporator temperature is considered as 4.5 °C whereas condenser temperature is taken from 40 °C to 60 °C in the interval of 4 °C. Different performance parameters have been calculated like total exergy destruction (TED), exergy destruction ratio (EDR), exergy efficiency, along with the coefficient of performance (COP) and efficiency defect. The result shows that R447A is found to be the potential alternative to replace R410A in the air conditioner as it has 9.24% higher COP and 15.38% less destruction of exergy along with 9.3% higher exergy efficiency compared to R410A at a condenser temperature of 60 °C. TED and EDR, are found to be minimum with the R447A system among all the considered refrigerants.